Role and regulation of heme iron acquisition in gram-negative pathogens - Runyen-Janecky, Laura J. (Frontiers in Cellular and Infection Microbiology, 2013)
Bacteria that reside in animal tissues and/or cells must acquire iron from their host. However, almost all of the host iron is sequestered in iron-containing compounds and proteins, the majority of which is found within heme molecules. Thus, likely iron sources for bacterial pathogens (and non-pathogenic symbionts) are free heme and heme-containing proteins. Furthermore, the cellular location of the bacterial within the host (intra or extracellular) influences the amount and nature of the iron containing compounds available for transport. The low level of free iron in the host, coupled with the presence of numerous different heme sources, has resulted in a wide range of high-affinity iron acquisition strategies within bacteria. However, since excess iron and heme are toxic to bacteria, expression of these acquisition systems is highly regulated. Precise expression in the correct host environment at the appropriate times enables heme iron acquisitions systems to contribute to the growth of bacterial pathogens within the host. This mini-review will highlight some of the recent findings in these areas for Gram-negative pathogens.